Effect of Omeprazole on Esophageal Microbiota in Dogs Detected Using a Minimally Invasive Sampling Method - Aditi Handa; Giovana S. Slanzon; Yoko M. Ambrosini; Jillian M. Haines (Journal of Veterinary Internal Medicine)
ABSTRACT Background Omeprazole alters the esophageal microbiome (EM) of humans and has associated effects. Objectives To assess the changes and subsequent recovery of the EM in awake dogs after omeprazole treatment, using the esophageal string test (EST). Animals Ten healthy, client‐owned adult dogs. Methods A prospective longitudinal design was employed, where esophageal samples were initially collected using EST (day 0), involving the oral administration of an EST capsule and subsequent retrieval after 15 min for pH‐based segment identification. The dogs were then administered 1 mg/kg of omeprazole orally, twice daily for 14 days. Follow‐up EST samplings were conducted on days 15 and 45. Samples were sequenced targeting the V3‐V4 region of the 16S rRNA gene and diversity analysis along with differential sequencing (DEseq2) was performed. Results All dogs tolerated the EST without adverse effects. The EST retrieved sufficient biofluid to characterize the EM in this group of dogs. Diversity analysis revealed no significant alterations in alpha (Observed species, Shannon and Simpson indices) and beta diversity (Bray‐Curtis) across the time points after omeprazole administration. Conclusions and Clinical Importance Omeprazole therapy did not alter the EM of healthy dogs in this study. The application of EST in dogs illustrates its use as a minimally invasive tool for investigating the role of EM in esophageal health and disease in dogs.